Nationalism and religion: Historical aspects of the relationship - Kyriakantonakis, Ioanni (The Historical Review/La Revue Historique, 2020)
Religion and nationalism are conventionally considered as the forces par excellence that have shaped, respectively, the traditional and modern worlds. This article presents the eclectic affinities between religion and nationalism, but it also goes beyond the historical dichotomy of religious pre-modernity versus nationalist modernity. It suggests that their relationship is not one-dimensional, rejecting the idea that nationalism is constructed solely with modern fabrics while religion only relates to the context of traditional society. Rather, it argues that the relationship between tradition and modernity is a dynamic one; this builds on a methodological framework that makes use of varied and even opposing theories of nationalism. The relationship is studied in different national and confessional contexts and eras, but it is mainly the association of Greek ethnicity/ nationalism and Orthodox Christianity that provides the empirical evidence for the theoretical argumentation.